Koperasi dalam Perspektif Hukum Islam (Telaah Kritis Pemikiran Hukum Islam Taqiyyuddin al-Nabhani) - Hamzah, Imron (Fakultas Syariah IAIN Purwokerto, 2017)
Cooperatives, originally emerging from the West, have grown in Muslim-majority countries, such as Indonesia. Modern Muslim scholars differ on the permissibility of cooperatives in Islamic law. Among the scholars who disallowed it is Taqiyyuddin al-Nabhani, who firmly declares that cooperative is not legal according Islamic law. The reason given by al-Nabhani is that within the cooperative there is no element of body as the subject of law, and also the distribution of profit in the cooperative is based on services that are not justified. But if it is analyzed carefully, it can be seen that in cooperatives there are already elements of the body in the form of board, and also the division of profit based on the service is essentially the division of profit based on work, so it is not contrary to the rules of Shari'a. This paper concludes that the cooperative is incorporated into the various contracts that have been discussed by the classical scholars, so the legal status of the cooperative is allowed according to Islamic law because there is no proposition forbids it.